2018
DOI: 10.1093/ijnp/pyy056
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cortical GABA and Loudness Dependence of Auditory Evoked Potentials (LDAEP) in Humans

Abstract: Loudness dependence of auditory evoked potentials (LDAEP) is a widely used EEG-based biomarker for central serotonergic activity. Serotonin has been shown to be associated with different psychiatric disorders such as depression and schizophrenia. Despite its clinical significance, the underlying neurochemical mechanism of this promising marker is not fully understood, and further research is needed to improve its validity. Other neurotransmitters might have a significant impact on this measure. Thus, we assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For instance, the administration of a glutamatergic NMDA antagonist has been reported to blunt LDAEP, suggesting that increased glutamatergic activity correlates with a heightened LDAEP (76). On the other hand, a study reported that the LDAEP is not associated with GABA levels (77). Further exploration of the relationships between ECT, auditory cortical activity, and excitatory and inhibitory neurotransmitters could yield valualbe insights.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the administration of a glutamatergic NMDA antagonist has been reported to blunt LDAEP, suggesting that increased glutamatergic activity correlates with a heightened LDAEP (76). On the other hand, a study reported that the LDAEP is not associated with GABA levels (77). Further exploration of the relationships between ECT, auditory cortical activity, and excitatory and inhibitory neurotransmitters could yield valualbe insights.…”
Section: Discussionmentioning
confidence: 99%
“…As conventionally done in LDAEP analysis, the first 5 responses to each of the 5 loudness levels were not included in the analysis. 6,10 Epochs of 800 ms were created (−200 ms before and 600 ms after stimulus onset). At least 30 artifact-free sweeps were taken as a requirement for creating the average event-related potential (ERP) for each loudness level.…”
Section: Eeg Recordingmentioning
confidence: 99%
“…8,9 Along similar lines, in a study combining magnetic resonance imaging with EEG to explore the gamma-Aminobutyric-acid (GABA)-ergic concentration and its ratio to glutamate in the primary auditory cortex, no effect of GABA on LDAEP was found. 10 However, blocking N-methyl-D-aspartate (NMDA) receptors pharmacologically reduced the LDAEP amplitude in both rhesus monkeys and healthy human participants. 11,12 Together, serotonin seems to act as the key player in LDAEP in the auditory cortex, with smaller effects of other transmitters such as NMDA on LDAEP.…”
Section: Introductionmentioning
confidence: 99%